Representações sociais da mulher em situação de violência doméstica e familiar no contexto sócio-histórico de São Borja/RS - Conto, Janete Maria de (2012)
This work tries to answer the following question: what are woman's social representation in a familiar and domestic violence situation in São Borja-RS' social historic context? The main objectives are to investigate and to interpret the social representation of woman that has been suffering or that had suffered agression by her partner/husband at home. This study interprets the social world and it tries to understand how representations that people construct, from its linguistics choices, exerts important roles in the organizational structures that construe the social life. In different circunstances, people give opinions, express value judgement and feelings, colaborating to create and to maintain a given social representation. Based on these assumptions, to do this etnografic qualitative research, a literature review was realized about the following theoretical perspectives: social genre (SAFFIOTI, 2001; 2004; 2009), social representation (MOSCOVICI, 1984; 1988; 2003), dialogicity (MARKOVÁ, 2006) e sociointeracionism (BAKHTIN, 1992; 1997). After that, statistics about domestic violence against women were identified, and effective legal actions such as Lei Maria da Penha and public policies established in São Borja's context to solve the problem were analysed. Specifically, in this research, the linguistic analysis focus on the genre Criminal Complaint (CC) about domestic violence against women and it was collected at São Borja's police court. Then, the textual genre was described, and twenty CCs were analysed. The results suggest that those documents show some pecularities and are caracterized by reported discourse and dialogicity, because it materializes the oral discourse reformulated by the written discourse of the police cleck. The woman's social representation registered in the Criminal Complaint highlights the comprehension and interpretation of the policial about the facts narrated by the victim. And, it is from this linguistic perception that violence against woman becomes public in the context investigated.